Proinsulin is stable at room temperature for 24 hours in EDTA: A clinical laboratory analysis (adAPT 3). - Jane Davidson; Timothy McDonald; Calum Sutherland; Mohammod Mostazir; Lidy VanAalten; Terence Wilkin (PLoS ONE)
Aims Reference laboratories advise immediate separation and freezing of samples for the assay of proinsulin, which limit its practicability for smaller centres. Following the demonstration that insulin and C-peptide are stable in EDTA at room temperature for at least 24hours, we undertook simple stability studies to establish whether the same might apply to proinsulin. Methods Venous blood samples were drawn from six adult women, some fasting, some not, aliquoted and assayed immediately and after storage at either 4°C or ambient temperature for periods from 2h to 24h. Results There was no significant variation or difference with storage time or storage condition in either individual or group analysis. Conclusion Proinsulin appears to be stable at room temperature in EDTA for at least 24h. Immediate separation and storage on ice of samples for proinsulin assay is not necessary, which will simplify sample transport, particularly for multicentre trials.